Identifying New Challenges and Emerging Issues in the Virtual Space during the COVID-19 Pandemic: A Systematic Review Based on Wright’s Model - Soltani, Zahra; Esmaeilishad, Behrang; Soleimanpour Omran, Mahboubeh (AI and Tech in Behavioral and Social Sciences, 2025)
The present study aimed to identify the new challenges and emerging issues in the virtual space during the COVID-19 pandemic in order to provide a comprehensive picture and perspective of this area. This qualitative research utilized a systematic review method. The research population consisted of all articles (179 articles) presented in the last five years on the challenges of virtual space and related fields in specialized and scientific databases. The sample for the study included 20 articles, selected purposefully based on thematic monitoring and theoretical saturation of the data. The research data were gathered through qualitative analysis of the documents under study. Through data analysis, the new challenges and emerging issues of the virtual space during the COVID-19 pandemic were categorized into 4 dimensions, 11 factors, and 56 categories. These included the dimension of socio-cultural challenges (identity disorder, value conflicts, social isolation); environmental challenges (changes in school work culture, transformation of organizational and product competitive advantages, emergence of educational inequities); ethical challenges (violation of privacy, cyber harassment, distortion of informational content); and educational challenges (incomplete teaching of laboratory courses, weakened sense of educational presence, educational frustration).